2016
DOI: 10.21037/tlcr.2016.06.10
|View full text |Cite
|
Sign up to set email alerts
|

Tackling ALK in non-small cell lung cancer: the role of novel inhibitors

Abstract: Abstract:Crizotinib is an oral inhibitor of anaplastic lymphoma kinase (ALK) with remarkable clinical activity in patients suffering from ALK-rearranged non-small cell lung cancer (NSCLC), accounting to its superiority compared to chemotherapy. Unfortunately, virtually all ALK-rearranged tumors acquire resistance to crizotinib, frequently within one year since the treatment initiation. To date, therapeutic strategies to overcome crizotinib resistance have focused on the use of more potent and structurally diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 115 publications
0
29
0
Order By: Relevance
“…Due to their ability to improve PFS and control brain metastases, these drugs are also frequently prescribed upfront. Third-generation ALK inhibitors including lorlatinib and ensartinib are currently investigated (8,9). Lorlatinib demonstrated clinical activity in resistant patients previously treated with two or more ALK inhibitors including second-generation inhibitors (10).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their ability to improve PFS and control brain metastases, these drugs are also frequently prescribed upfront. Third-generation ALK inhibitors including lorlatinib and ensartinib are currently investigated (8,9). Lorlatinib demonstrated clinical activity in resistant patients previously treated with two or more ALK inhibitors including second-generation inhibitors (10).…”
Section: Introductionmentioning
confidence: 99%
“…Anaplastic lymphoma kinase (ALK), known as ALK tyrosine kinase receptor or cluster of differentiation 246 (CD246), has been identified as one of the major oncogenes in tumor pathogenesis [8, 11, 12, 16, 21, 26, 51]. In NB, high expression levels of ALK closely correlates with poor outcomes, especially in high-risk NB [22, 42, 49].…”
Section: Introductionmentioning
confidence: 99%
“…(18,25) The EML4-ALK fusion oncoprotein requires an N-terminal coiled-coil domain of EML4 which is essential for dimerization of the fusion protein and constitutive activation of ALK kinase. (26) Tyrosine kinase inhibitors binding to an ATP-binding pocket of ALK, such as crizotinib, (27) ceritinib, (28)(29)(30)(31) and alectinib, (32,33) have been proven their clinical effectiveness for NSCLC with genetic alterations causing aberrant ALK activation. It was also reported that SUMOylation and glycosylation on the NPM-ALK rearranged oncoprotein affected the stability and phosphorylation of the fused protein in neuroblastoma.…”
mentioning
confidence: 99%